Physicochemical and Sensory Attributes of Robusta Coffee as Influenced by Sorbitol Concentration and Roasting Time - Hidayat, Dadang D.; Ikrawan, Yusep; Harin, Natasha Yollandita; Furqon, Maulana; Rahayuningtyas, Ari; Sudaryanto, Arie; Sagita, Diang (Indonesian Coffee and Cocoa Research Institute, 2023)
Many studies have reported several methods to improve the quality of Robusta coffee such as fermentation, but it takes a relatively long time. In this study, a new processing method for Robusta coffee quality enhancement was investigated. Robusta coffee cherry was immersed using sorbitol solution under different concentrations (10%, 15%, and 20%), then the green bean coffee was roasted with several roasting duration (1, 3, and 5 minutes after coffee beans cracking) to determine the characteristic of coffee produced. Characteristics examined were chemical responses consisted of water content, pH, caffeine content, and anti- oxidant activity (IC50); physical responses consisted of L* color attribute; and organoleptic responses consisted of color, aroma, taste, and aftertaste. Principal component analysis (PCA) was employed to examine the qualitative correlations between dependent variables. The results demonstrated that the concentration of sorbitol of 10% to 20% altered the organoleptic reaction but not the physical and chemical responses. The roasting time impacted the coffee’s water content, pH, antioxidant activity (IC50), color, flavor, and aftertaste, but not its caffeine content and aroma. The interaction between sorbitol concentration and roasting time influences the color, flavor, and aftertaste characteristics of coffee. This finding led to an improvement in the quality of Robusta coffee. Furthermore, PCA showed that IC50 value was positively correlated with pH value and was conversely correlated with water content and L*, and slightly correlated with caffeine. Sensory attributes had no correlation with variables of IC50, caffeine and pH, and L*.